(untitled) (Cadernos de Sociomuseologia, 2021)
The Museu Paulista established its collection policy in 1990, at the same time as the institution’s research line was as follows: I. Daily life and society (sexual roles, age and enculturation), II. The World of Work (pre and proto-industrial) and III. Imaginary (the material vectors of sense). During my master’s research, after analysing approximately 617 acquisition processes, I was able to identify that the institution collects a considerable number of objects because of its interest in gender issues. However, even after 25 years of work in this area the Museu Paulista continues to consider the binary concept of gender. This results in the exclusion of references to non-binary aspects of gender and sexual diversity in the museum’s collection, as well as the removal of the institution of contemporary studies on gender and sexual roles. We must point out that the Museu Paulista is not the only one to develop its institutional policy in this way. In Brasil, at least some authors have already shown that museums are, for the most part, far removed from the discussion about gender and sexual diversity. This is one of the main reasons justifying the discussion on the international scene, in addition to the fact that ’new’ identities of gender and sexuality have been the subject of intense public debate nowadays. Key words: Museology; Sexual diversity; History museum; Collections acquisition.